Combining fecal microbiome and metabolomics to reveal the disturbance of gut microbiota in liver injury and the therapeutic mechanism of shaoyao gancao decoction - Li, Jingwei; Zhao, Min; Li, Jianming; Wang, Miao; Zhao, Chunjie (Frontiers in Pharmacology, 2022)
Chemical liver injury is closely related to gut microbiota and its metabolites. In this study, we combined 16S rRNA gene sequencing, 1H NMR-based fecal metabolomics and GC-MS to evaluate the changes in gut microbiota, fecal metabolites and Short-chain fatty acids (SCFAs) in CCl4-induced liver injury, and the therapeutic effect of Shaoyao Gancao Decoction (SGD). The results showed that CCl4-induced liver injury overexpressed CYP2E1, enhanced oxidative stress, decreased antioxidant enzymes (SOD, GSH), increased peroxidative products MDA and inflammatory responses (IL-6, TNF-α), while SGD treatment was reverse. H&E staining showed that SGD could alleviate liver tissue lesions, which was confirmed by the recovered liver index, ALT and AST. Correlation network analysis indicated that liver injury led to a decrease in microbiota correlation, while SGD helped restore it. In addition, fecal metabolomic confirmed the PICRUSt results that liver injury caused disturbances in amino acid metabolism, which were modulated by SGD. Spearman’s analysis showed that liver injury disrupted ammonia transport, urea cycle, intestinal barrier and energy metabolism. Moreover, the levels of SCFAs were also decreased, and the abundance of Lachnoclostridium, Blautia, Lachnospiraceae_NK4A136_group, UCG-005 and Turicibacter associated with SCFAs were altered. However, all this can be reversed by SGD. More importantly, pseudo germ-free rats demonstrated that the absence of gut microbiota aggravated liver injury and affected the efficacy of SGD. Taken together, we speculate that the gut microbiota has a protective role in the pathogenesis of liver injury, and has a positive significance for the efficacy of SGD. Moreover, SGD can treat liver injury by modulating gut microbiota and its metabolites and SCFAs. This provides useful evidence for the study of the pathogenesis of liver injury and the clinical application of SGD.